Analisis Tahapan dan Faktor Pendukung Perkembangan Bahasa Anak Usia Dini - Rts Selsa Tri Novelina; Nadia Riski Edriani; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Language development in early childhood progresses through systematic stages, starting from the pre-linguistic phase to mastering complex language similar to adult speech. This process involves various bodily organs such as the brain, vocal cords, and ears that work together in language processing and production. Language acquisition is influenced by the interaction of competencies in understanding and producing utterances, which include observation, interpretation, and sentence generation. External factors such as parental roles, social environment, peers, and communication activities are key determinants of successful language development. Differences in language ability among children arise from a combination of biological maturity and social dynamics. This study employs a qualitative literature review method to synthesize theories and previous research findings related to children's language development. The comprehensive findings emphasize the importance of early stimulation and a conducive environment to support optimal language growth, which is crucial for educational success and social adaptation.